MBRS-63. THE ROLE OF THE SWI/SNF COMPLEX SUBUNIT SMARCD3 IN MEDULLOBLASTOMA. (4th December 2020) - Poore, Brad; Zou, Han; Sharma, Vaibhav; Pollack, Ian; Hu, Baoli
Abstract: Medulloblastoma is the most common malignant brain tumor in children, with the Group 3 (G3) having the worst prognosis of the subgroups (WNT, SHH, and Group 4). We aimed to determine the underlying differences between G3 and the other subgroups, with an emphasis on genes that control the epigenome for developing effective treatments for patients with this disease. To this end, we found that G3 has elevated expression of the SWI/SNF subcomponent, SMARCD3 (P<0.001), which serves to guide the SWI/SNF complex to different genomic regions through interactions with various transcription factors. However, little is known about function of SMARCD3 in cancer, particularly in medulloblastoma. Clinically, elevated SMARCD3 mRNA resulted in a poorer prognosis in medulloblastoma patients (P<0.0001), which was further validated in 63 patient tumors by immunohistochemical staining for SMARCD3. Interestingly, tumors that had metastasized often had elevated expression of SMARCD3, in all subgroups of medulloblastomas (P<0.0001) and G3 only (P<0.01) based on analyzing multiple published databases. An orthotopic mouse model further supported that SMARCD3 is highly expressed in metastatic tumors compared to primary tumors. Importantly, CRISPR-CAS9-mediated SMARCD3 deletion decreased cell migration in medulloblastoma cell lines. Mechanistically, SMARCD3 deletion led to decreased H3K27me3, suggesting that SMARCD3 may cooperate with PRC2 in regulation of gene expression. Together, our results indicate that SMARCD3 plays a significant role in the development of metastatic dissemination in medulloblastoma, especially in the G3 subgroup. Thus, targeting the SMARCD3-containing SWI/SNF Complex may effectively prevent tumor dissemination and improve clinical outcomes in children with medulloblastoma.